The Effectiveness of Discovery Learning Method on Reading Descriptive Text at Eighth Grade of SMP Diniyah Al Falahiyah Lamongan - Muhammad Luthfi Abdillah (Academia Publication, 2021)
This researcher measures the effectiveness of discovery learning on reading descriptive text at eight grades of SMP Diniyah Al Falahiyah Lamongan in academic 2020/202. The discovery learning method strategy works for the students' mental, easy to interact (actively) and new information independently. The method of the research utilized a quantitative experimental method by using a pre-experimental design. Conducted the sample of the study was at VII-A class with 30 students. The instrument of collecting data used try-out and test (pre-test and post-test). The test had utilized to know students' abilities before and after the experiment run. The result of the research showed the mean score in the pre-test was 57.33, and the post-test was 74.50. The result was that the post-test was higher than the pre-test. The analysis using the SPSS based paired sample t-test formula produces a significance value of sig. (2-tailed) had 0.000 at the critical value for the 5% level (0.000 < 0.05). The obtained t-test had -21.908, and the t-table was 2.042. So, the test score was higher than the t-table (-21.908 > 2.042). It means rejected Ho and Ha is accepted. It can conclude that the discovery learning method has significant and effectiveness to reading descriptive text.